Synthesis, Characterization, Optical and Dielectric Properties of NiO and Zn‐Doped NiO Nanostructures: Toward Advanced Applications - Ali, Atizaz; Ahmad, Sohail; Usman, Muhammad; Khan, Nangyaley; Hashim, Muhammad; Ali, Yasir; Shah, Rasool; Rahman, Naveed Ur (Advances in condensed matter physics, 2024)
In this current study, hydrothermal method was employed to synthesize distinct nanostructures: pure nickel oxide (NiO), Zn‐doped NiO, and NiO/ZnO composites. X‐ray diffraction (XRD) results confirmed NiO’s cubic structure, with sizes of 17.01 nm for pure NiO and 30.87 nm for composites. Scanning electron microscope (SEM) images revealed flowerlike morphologies, energy‐dispersive X‐ray spectroscopy (EDX) authenticated the elemental composition without any impurities. Ultraviolet–visible (UV‐Vis) spectroscopy demonstrated heightened absorption in doped and nanocomposite samples. The bandgap energy calculated using Tauc’s plot reduced from 2.95 to 2.55 eV with increase in zinc (Zn) content. In Fourier‐transform infrared (FTIR) characterization, the Ni–O stretching vibration appeared at 666.7 cm −1 in doped samples, while Zn–O stretching was evident at 586.03 cm −1 . Photoluminescence analysis unveiled a strong peak at 470 nm (near band edge) and another at 665 nm (indicative of defects), exhibiting intensified signals in doped and nanocomposite samples due to a higher defect density. The dielectric constant showed increased values at low frequencies attributed to real and space charge polarization. Notably, the conductivity of Zn‐doped and nanocomposite samples displayed an upward trend with frequency due to a higher defect density. This study unveils insights into the intricate optical and electrical properties of these novel nanostructures, showcasing their potential in advanced energy storage applications.